Menakar Pembaharuan Pendidikan Muhammad Abduh - Muhammad Nasihuddin (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2020)
Muhammad Abduh is a figure of 19th-century Islamic reformer who promotes religious rationality. As a reformer, Muhammad ‘Abduh views education as an important element for the Islamic community to regain its long-lost dignity. Muhammad ‘Abduh wanted to play a role in the revival of the civilization of the people who were being hit by the storm of backwardness. He saw that the road to that was